1981
DOI: 10.1111/1523-1747.ep12525394
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Papillomaviruses in Butchers' Warts

Abstract: We have studied the papillomaviruses found in the hand warts of 60 butchers, most of them from 2 distant slaughterhouses. Warts differing in morphology and location were studied separately. The viruses were identified by molecular hybridization, restriction enzyme analysis and immunofluorescence. Four known human papillomaviruses (HPV-1, HPV-2, HPV-3, HPV-4) were detected and one hitherto unknown papillomavirus was identified in 9 butchers. The DNA of the latter virus did not anneal with any of the RNAs comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(46 citation statements)
references
References 30 publications
1
45
0
Order By: Relevance
“…Interestingly, these two tumors also harbored either HPV 6 (18,19), and a nonintegrated episomal state (9) characterize the isolates obtained thus far. (20,21) renders identity with the cervical papillomavirus DNA rather unlikely. The The DNA showed some heterogeneity in cancer tissue, suggesting either the existence of various subtypes or genomic rearrangements during cancer development.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, these two tumors also harbored either HPV 6 (18,19), and a nonintegrated episomal state (9) characterize the isolates obtained thus far. (20,21) renders identity with the cervical papillomavirus DNA rather unlikely. The The DNA showed some heterogeneity in cancer tissue, suggesting either the existence of various subtypes or genomic rearrangements during cancer development.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of virus warts among slaughterhouse workers, including poultry slaughterhouse workers (40)(41)(42)(43)(44)(45), has been assessed in several studies and shows the following patterns: (i) the prevalence of virus warts among slaughterhouse workers is generally high, 24-47%; (ii) in studies which allow comparison with unexposed groups, there is a prevalence ratio of about 3; (iii) the high prevalence of virus warts is found in all departments of slaughterhouses, but one study (45) found a higher prevalence (47%) among "meat handlers" than among "non meat handlers," (31%).…”
Section: Which Exposures In the Work Environment Could Possibly Explamentioning
confidence: 99%
“…The warts may derive from infection with various types of human papilloma virus (40). The slaughtered animals may act as vectors for the infection from one worker to another.…”
Section: Which Exposures In the Work Environment Could Possibly Explamentioning
confidence: 99%
“…Verruca vulgaris (VV), common wart or viral wart, is a virus-induced neoplasm of the skin caused by a human papillomavirus (HPV). As currently known, verruca vulgaris is associated with HPV types 2 and 4, flat warts with HPV-3 and 10, and Butchers' warts with HPV-7 [3][4][5]. Oral verruca vulgaris (OVV) lesions appear similar to their cutaneous counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor occurs at any age, with a preference in children and involves the vermilion and mucous membranes of the oral cavity. Presence of HPV in the oral cavity has been demonstrated by means of electron microscopy, immunohistochemistry and molecular biology methods [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%